MENINGKATKAN KINERJA PROTOKOL ROUTING AOMDV UNTUK MENCARI RUTE BERDASARKAN PERGERAKAN NODE DAN MENGURANGI BROADCAST STORM DALAM JARINGAN MANET - Mei Sukriani; Andy Hidayat Jatmika; Raphael Bianco Huwae (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2025)
Rapid topology changes in Mobile Ad Hoc Networks due to node movement often cause network instability. Each node in the network can move freely with varying speeds in different directions. As a result, the connection between devices can be disconnected or reconnected depending on the different communication ranges. Node movement causes constraints on the communication path created by AOMDV, because it does not take into account node mobility, so AOMDV has difficulty in maintaining route stability. This study aims to improve the performance of the AOMDV routing protocol in MANET by using the TimePrediction algorithm to improve the calculation of node movement during the route search process. This approach involves modifying the "Hello" message so that the position and speed information of neighboring nodes, which will be sent gradually to ensure communication between nodes. adding location and speed information of each device into the message that will be sent by each other. The TimePrediction protocol was created to overcome the problem of a constantly changing network. By predicting where nodes in the network will move, this protocol can also create a more stable communication path. The results showed that the TimePrediction AOMDV protocol successfully increased the average throughput by 5.39% for 50 nodes, 6.48% for 75 nodes, and 6.87% for 100 nodes. In addition, the average end-to-end delay decreased by 5.39% for 50 nodes, 6.48% for 75 nodes, and 6.87% for 100 nodes. The packet delivery ratio also increased by an average of 7.19% for 50 nodes, 8.80% for 75 nodes, and 12.70% for 100 nodes.